1979
DOI: 10.1056/nejm197907123010202
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid-Induced Hypertension in Patients with Orthostatic Hypotension

Abstract: The mechanism of recumbent hypertension induced by fludrocortisone was studied in seven patients with orthostatic hypotension. All showed increases in blood pressure in the recumbent and standing positions, and hypertensive levels were achieved on recumbency in four of them. Hypertensive retinopathy developed in two patients and cardiomegaly in one. Initial blood-pressure elevations were associated with sodium retention and plasma-volume expansion. However, with long-term treatment, plasma volume decreased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(103 citation statements)
references
References 22 publications
1
101
0
1
Order By: Relevance
“…This is well in agreement with the recent study by Maule et al [20] who reported that the development of left ventricular hypertrophy in patients with MSA does not depend on years of disease and treatment for orthostatic hypotension. The pathophysiology of supine hypertension in MSA appears to be more complex, including baroreflex dysfunction, nocturnal fluid retention, adrenergic hypersensitivity, or drug treatment for orthostatic hypotension [5]. Among the causes mentioned, it was recently recognized that in patients with MSA, supine hypertension might reflect part of the pathophysiology of primary chronic autonomic failure, and residually increased sympathetic tone is a major contributor to supine hypertension regardless of pressor agent use [31].…”
Section: Discussionmentioning
confidence: 99%
“…This is well in agreement with the recent study by Maule et al [20] who reported that the development of left ventricular hypertrophy in patients with MSA does not depend on years of disease and treatment for orthostatic hypotension. The pathophysiology of supine hypertension in MSA appears to be more complex, including baroreflex dysfunction, nocturnal fluid retention, adrenergic hypersensitivity, or drug treatment for orthostatic hypotension [5]. Among the causes mentioned, it was recently recognized that in patients with MSA, supine hypertension might reflect part of the pathophysiology of primary chronic autonomic failure, and residually increased sympathetic tone is a major contributor to supine hypertension regardless of pressor agent use [31].…”
Section: Discussionmentioning
confidence: 99%
“…The following drugs were used: acetylcholine hydrochloride (Sigma, St. Louis, MO, USA); adenosine 5'-diphosphate (ADP; Sigma); sodium heparin (Elkin Sinn, Cherry Hill, NJ, USA); 5-hydroxytryptamine All drugs were dissolved in distilled water, except indomethacin, which was dissolved in 10 ml of distilled water containing 5 X 10" 3 M NaCO 3 and was sonicated before use. The drugs were added to the organ chambers in volumes of 500 /xl or less.…”
Section: Drugsmentioning
confidence: 99%
“…18 It is postulated that mineralocorticoids elevate blood pressure mainly by increasing total peripheral resistance and vascular reactivity to catecholamines in humans, with a tendency to suppress circulating catecholamines. 19 ' 20 In addition, neither measurements of plasma catecholamine levels nor analysis of the cardiovascular responses to sympatholytic agents in patients with PA have afforded any evidence of enhanced peripheral sympathetic activity mineralocorticoid-excess hypertension. 21 These findings and our recent preliminary findings, which show an increase of MSNA after adrenalectomy in PA patients (unpublished observation from our laboratory), are in line with the results indicating that sympathetic nerve activity was rather suppressed in PA patients.…”
mentioning
confidence: 99%